Effect of natural polyphenols on diabetes mellitus (type-2) with myocardial infarction: a double-blind placebo controlled trial - Goyal, Rahul; Nagtilak, S.; Thawani, Vijay; Jindal, Shavetika (International Journal of Advances in Medicine, 2019)
Background: Diabetes Mellitus Type-2(T2D); is a leading disease in world wide. T2D is a clinical syndrome characterized by hyperglycaemia. Hyperglycemias are caused by an absolute or relative deficiency of insulin and due to insulin resistance. Diabetic patients are highly prone to Reactive Oxygen Species (ROS) and leads to Cardio vascular complications. Several medicines have been recommended to cure T2D; and still discovery of newer drugs are in process. Now a day, the focus of researches in diabetes includes discovery of newer anti-diabetic agents as well as isolating the active compounds from herbal sources. One such herbal source is pomegranate. Pomegranate is polyphenols and antioxidants rich fruit; which has potency to cure T2D and ROS. Methods: A Pomegranate Extract of Whole Fruit (PEWF) was prepared as tablet of 300mg to investigate its effects in patients with T2D. Total 40 participants of either gender with nested cases of T2D with Myocardial Infarction (MI) were included in study. All participants were assigned in two groups (20 each). One group was under “Add On” therapy of PEWF and matching placebos of same colour, shape and size were used as comparator agent for second group (300mg BD for 1 month). Results: Levels of biochemical markers related to T2D were compared to analysed pre and post drug effects by Z test, chi square test and by coefficient of variations. Results highlighted that those participants who were under “add-on” therapy of PEWF showed highly prognostic significance. Thus, PEWF should be consumed in diet as food supplementation. Conclusions: In conclusion, polyphenols and antioxidants rich fruit supplements should be taken in diet for healthy living.